Enantioselective Allylic Substitution of Morita–Baylis–Hillman Adducts Catalyzed by Chiral Bifunctional Ferrocenylphosphines. Issue 12 (6th April 2016) - Zhu, Linglong; Hu, Haiwen; Qi, Liang; Zheng, Yi; Zhong, Weihui
Abstract: A series of air‐stable chiral ferrocenylphosphines (LB1 –LB4 ) were prepared and used in the asymmetric allylic substitution of Morita–Baylis–Hillman (MBH) adducts with phthalimide under mild reaction conditions; the ( R, S Fc )‐ferrocenylphosphineLB4 afforded the desired amination products3 in moderate yields with excellent enantioselectivities. The absolute configuration of3o was confirmed by X‐ray analysis. Abstract : The air‐stable chiral ferrocenylphosphineLB4 promotes the asymmetric allylic substitution of Morita–Baylis–Hillman (MBH) adducts with phthalimide to afford amination products3 in moderate yields with excellent enantioselectivities. The absolute configuration of3 was determined by X‐ray analysis.